2008
DOI: 10.1007/s10725-008-9337-9
|View full text |Cite
|
Sign up to set email alerts
|

The rate of cellulose increase is highly related to cotton fibre strength and is significantly determined by its genetic background and boll period temperature

Abstract: This experiment was conducted to study the relationship between the increase in cellulose content in developing cotton bolls and their final cotton fibre strength. The rate of cellulose increase over time was estimated using logistical regression, and the logistic equation parameters were then used to compare different cotton cultivars in different temperature environments. The increase in cellulose content followed a typical ''S'' curve, with the boll period time divided into slow-fast-slow stages. In differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…Numbers of studies have reported that sowing date affected cotton yield and fiber quality, but the results were always inconsistent (Porter et al, 1996;Dong et al, 2006;Wang et al, 2009). In our experiment, sowing dates significantly affected cotton boll weight and fiber quality especially fiber strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numbers of studies have reported that sowing date affected cotton yield and fiber quality, but the results were always inconsistent (Porter et al, 1996;Dong et al, 2006;Wang et al, 2009). In our experiment, sowing dates significantly affected cotton boll weight and fiber quality especially fiber strength.…”
Section: Discussionmentioning
confidence: 99%
“…Bradow et al (1997) indicated that fiber length varied among fruiting sites. Wang et al (2009) indicated that fiber strength varied among the boll inserted location. Extensive investigations have been carried out on the effects of sowing date or boll position on cotton fiber development respectively, and Davidonis et al, (2004) investigated boll location × planting date effects on fiber quality.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the report of Wang et al (2008Wang et al ( , 2009) who divided cotton (Gossypium hirsutum L.) into temperaturesensitive groups, two contrasting cultivars, Kemian 1 (cool temperature-tolerant) and Sumian 15 (cool temperaturesensitive) were selected for this study. Different environmental conditions during fibre developing periods were provided by sowing cotton on different dates, 25 April, 25 May and 10 June in 2010 and 2011.…”
Section: Experimental Designmentioning
confidence: 99%
“…Several overlapping developmental phases lead to the formation of mature cotton fibers: initiation, elongation, secondary cell wall deposition, and finally maturation (Seagull et al 2000;Jasdanwala et al 1977;Kim and Triplett 2001;Wang et al 2009). The day of flowering is referred to as anthesis and the term ''days post-anthesis'' (dpa) is often used to describe the cotton fiber development.…”
Section: Introductionmentioning
confidence: 99%